Challenging the European Union: a critical metaphtonymic analysis of Viktor Orbán’s speeches (2015–2021) (Philology, 2024)
This paper aims to carry out a critical metaphtonymic analysis of Hungarian Prime Minister Viktor Orbán’s speeches related to the European Union (EU). It offers a theoretical model to explore how the Hungarian prime minister constructs his image of Europe’s strongman, challenging the EU. The theoretical and methodological framework lies in the cross-fertilization of the studies of A. Barcelona, G. Radden, Z. Kövecses, G. Lakoff, and M. Johnson, to mention but a few. As a key figure in Europe's rise of illiberalism, under Viktor Orbán’s rule Hungary has become a hybrid system of autocracy, eroding democratic institutions while benefiting from EU membership. The paper sums up research in the field of political studies and discusses Orbán's strategies to consolidate power, exploit EU funding, and foster crony capitalism, while arguing that the EU's response to Hungary's democratic backsliding has been slow, reactive, and ineffective. Suggestions are made that the EU needs stronger mechanisms and more decisive actions. Orbán’s foreign policy pragmatism further complicates the EU’s efforts, raising concerns about the stability of the union and the future of European values. The findings arrived at in this article suggest that metaphtonomy is used to connect Hungary’s historical struggles with its contemporary challenges, portraying the country as a defender of European sovereignty, and contrasting its nationalist stance with a declining, imperialistic EU. Thus Orban’s rhetoric positions Hungary as a moral and cultural leader in Europe, using emotional appeal to gain public support for his policies.
Keywords: critical metaphtonymic analysis; political speech; Viktor Orbán; Hungary; the European Union